Comparison Between Natural and Synthetic Antioxidants in Beef Products: A MetaAnalysis - K. A. Fadhil; T. Suryati; A. Jayanegara (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
Synthetic antioxidants are created through artificial synthesis, whereas natural antioxidants are created through natural synthesis in plants, animals, and microbes. Although synthetic antioxidants have been used previously, there has been a growing need in recent years for natural antioxidants, largely due to the negative consequences of synthetic antioxidants. Therefore, many current studies have focused on finding natural antioxidants in diverse plants. This study aimed to compare the effectiveness of natural and synthetic antioxidants in beef products using a meta-analysis approach. The method included the stages of identification, selection, and conformity check. The selection process resulted in 12 articles obtained from the electronic database of Harzing’s Publish and Perish software. The metaanalysis model used in this study was random-effect model involving a positive control group (synthetic antioxidants) and an experimental group (natural antioxidants). The effect size and confidence interval were computed using the OpenMEE software, while the summary size and Egger’s test were obtained using JASP software. Results revealed that the addition of natural antioxidants showed comparable quality to synthetic antioxidants, as indicated by similar values between the two groups for the peroxide value, carbonyl content, metmyoglobin content, cooking loss, pH, and hue angle (P>0.05). Natural antioxidants showed a higher value on b (yellowness) and chroma (P<0.05). Parameters indicating lower value (P<0.05) occurred in TBARS, a (redness), and L (lightness). In conclusion, the addition of natural antioxidants in beef products demonstrates comparable results and could be used as alternatives to synthetic antioxidants.